Large-scale private investors, yield, farm income and food security in Ghana: evidence from continuous treatment approach - Abdallah, Abdul-Hanan (Frontiers in Environmental Economics, 2025)
IntroductionThis study investigates the effect of training hours received from Large-Scale Private Investors (LSPIs) on rice yield, farm income, and food security among smallholder farmers in Ghana. With the expansion of LSPIs in agricultural service delivery, identifying the optimal intensity of extension services is key to maximizing their impact.MethodsUsing data from rice-producing households, the study applies a dose-response function (DRF) and marginal treatment effect (MTE) analysis to estimate the non-linear effects of LSPI-provided training hours on key welfare outcomes. These models allow us to explore threshold effects and heterogeneous treatment responses.Results and discussionFindings show that rice yields peak with 1–3 h of training, after which additional interaction yields minimal gains. Farm income increases significantly beyond 4.5 h of training, with the highest returns at 6 h. Food security improves notably after 4 h, as measured by both the Food Consumption Score (FCS) and the Household Food Insecurity Access Scale (HFIAS). Beyond these thresholds, further training produces little to no additional benefit. These results emphasize the importance of well-timed, targeted training. Policymakers and LSPI programs should align training delivery with identified optimal durations and ensure appropriate follow-up mechanisms to sustain improvements in productivity and wellbeing.